Protein and Calcium Adequacy Levels as Dominant Factors In The Incidence Of Stunted Primary School Students In Coastal Areas - Samuel, Samuel; Saragih, Mariana; Sholichin, Sholichin (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Stunting does not only occur in toddlers but also affects children of primary school age. The 2018 Basic Health Research (RISKESDAS) reported that the prevalence of stunting among children aged 5–12 years was 23.6%, indicating that it remains a public health problem. Objectives: This study aimed to analyze stunting among primary school students in coastal areas in relation to nutritional adequacy for growth. Method: A cross-sectional study was conducted among primary school students in coastal areas. Data were collected on the adequacy levels of energy, protein, vitamin C, calcium, phosphorus, zinc, and iron intake. Data were analyzed using chi-square tests and logistic regression to identify dominant risk factors. Results: The prevalence of stunting among primary school students in coastal areas was 12.5%, with a higher proportion among females (8.3%). Risk factors associated with stunting included inadequate energy intake (PR = 4.4; 95% CI: 1.3–15.2), protein (PR = 29.3; 95% CI: 7.1–119.8), calcium (PR = 8.1; 95% CI: 2.4–37.5), phosphorus (PR = 7.9; 95% CI: 1.1–58.4), and zinc (PR = 23.2; 95% CI: 5.6–96.5). Multivariate analysis showed that inadequate protein and calcium intake were the dominant factors associated with stunting. Conclusion: Inadequate protein and calcium consumption are the dominant determinants of stunting among primary school students in coastal areas. Nutritional interventions focusing on improving protein- and calcium-rich food intake are strongly recommended.